Branched‐chain amino acids at supraphysiological but not physiological levels reduce myotube insulin sensitivity. Issue 2 (24th August 2021) - Rivera, Madison E.; Rivera, Caroline N.; Vaughan, Roger A.
Abstract: Aims: Branched‐chain amino acids (BCAA) are often emphasized in the diets of avid exercisers, yet population data demonstrates a correlation between circulating BCAA and insulin resistance. However, it is unclear if BCAA independently promote insulin resistance in otherwise healthy cells. The purpose of this study is to examine the effect of a BCAA mixture on muscle insulin signaling in vitro in both insulin resistant and sensitive cells. Materials and Methods: C2C12 myotubes were treated with a BCAA mixture containing leucine:isoleucine:valine at a ratio of 2:1:1 at 0.2, 2, or 20 mM (based on leucine content) for either 30 min, 1 day, or 6 days. Western blot was used to assess insulin sensitivity of cells treated with BCAA both with and without concurrent insulin resistance, and, with and without insulin stimulation. Results: BCAA treatment for 1 day significantly reduced basal, but not insulin‐stimulated pAkt expression. BCAA treatment for 6 days resulted in significantly reduced basal insulin signaling in healthy cells and insulin‐stimulated insulin signaling in insulin resistant (but not insulin sensitive) cells. Conclusion: Similar to previous observations demonstrating BCAA may correlate with insulin resistance during metabolically stressed conditions, we demonstrate excessively high BCAA exposure can negatively influence basal insulin signaling, as well as insulin sensitivity in insulin resistant myotubes. However, given the intentionally high concentrations of BCAA used in this study, the extent to which these observations translate to in vivo models is unclear and warrants further investigation.